IMPLEMENTASI KAMERA PEOPLE COUNTING PADA TEMPAT IBADAH DALAM UPAYA MENCEGAH PENYEBARAN COVID-19 - Acarya Mordekhai Karang, M; Oka Widyantara, I M; Diafari Djuni H, I G A K (Jurnal SPEKTRUM, 2021)
The COVID-19 pandemic results in activities that are actually being carried out or eliminated. The government has made efforts to keep activities running, one of which is by limiting the number of congregations attending to a maximum of 20% (twenty percent) of the room capacity and no more than 30 people. To be able to find out the number of congregants present in a building, a HIKVision People Counting Camera is used which is able to calculate the rate of people entering a building. The use of the People Counting Camera is expected to be able to control the number of congregants who attend. The ability of this camera is expected to be able to control the number of congregants who attend places of worship so that worship can comply with proper health protocols.